Peran Budaya Kerja, Lingkungan Kerja, Disiplin Kerja, Kompensasi Dan Keahlian Terhadap Kinerja Karyawan Pada PT. Mega Briquette Ungaran - Sukardi Sukardi (FEB UNTAG Semarang, 2018)
The purpose of this study was to determine the effect of work culture, work environment, work discipline, compensation, and expertise on the performance of company employees. Based on this, this research takes the title